A history of concussions is associated with symptoms of common mental disorders in former male professional athletes across a range of sports. Issue 4 (2nd October 2017) - Gouttebarge, Vincent; Aoki, Haruhito; Lambert, Michael; Stewart, William; Kerkhoffs, Gino
ABSTRACT: Objective : Recent reports suggest that exposure to repetitive concussions in sports is associated with an increased risk of symptoms of distress, anxiety and depression, sleep disturbance or substance abuse/dependence (typically referred as symptoms of common mental disorders[CMD]) and of later development of neurodegenerative disease, in particular chronic traumatic encephalopathy (CTE). The primary aim of this study was to explore the relationship between sports career-related concussions and the subsequent occurrence of symptoms of CMD among former male professional athletes retired from football (soccer), ice hockey and rugby (union). Methods : Cross-sectional analyses were performed on baseline electronic questionnaires from three prospective cohort studies among former male professional athletes retired from football (soccer), ice hockey and rugby (union). The number of confirmed concussions was examined through a single question, while symptoms of distress, anxiety and depression, sleep disturbance and adverse alcohol use were assessed using validated questionnaires. Results : From 1, 957 former professional athletes contacted, a total of 576 (29%) completed the questionnaire. Of these, 23% had not incurred a concussion during their career, 34% had two or three, 18% four or five, and 11% six or more concussions. The number of sports career-related concussions was a predictor for all outcome measures (β = 0.072–0.109; P ≤ 0.040). Specifically, former professional athletes who reported a history of four or five concussions were approximately 1.5 times more likely to report symptoms of CMD, rising to a two- to five-fold increase in those reporting a history of six or more sports career-related concussions. Conclusions : These data demonstrate an association between exposure to sports concussion and subsequent risk of symptoms of CMD in former professional athletes across a range of contact sports. Further work to explore the association between sports concussion and symptoms of CMD is required; in the meanwhile, strategies for effective risk reduction and improved management appear indicated.